MEMBANGUN KARAKTER SPIRITUAL MELALUI HADIS NABI: STUDI HADIS TEMATIK ATAS KONSEP ZUHUD - Alifya; Maftuh Ajmain; Muhammad Alif; Repa Hudan Lisalam (AL-BAYAN INSTITUTE, 2025)
Modern life, which is full of materialism and hedonism, has caused a crisis of meaning in life, moral degradation, and a weakening of spiritual character in society. This study aims to examine the role of the hadith of the Prophet Muhammad SAW, especially the concept of zuhud, in building the spiritual character of Muslims amid the challenges of the times. This research employs a qualitative approach using thematic hadith analysis and grounded theory, with primary data sourced from digital hadith collections and secondary literature from books and scientific journals. The results of the study indicate that spiritual character is the main foundation for the formation of morality, ethics, and inner peace in individuals. The concept of zuhud in the Prophet's hadith does not teach total rejection of the world, but rather emphasizes self-control from excessive love of material things and prioritizes the values of the hereafter. Zuhud values such as simplicity, contentment, and orientation toward the hereafter have proven relevant in shaping an integrity-based personality, strengthening social empathy, and enhancing decision-making quality grounded in Islamic teachings. Thus, the implementation of zuhud values through an understanding of the Prophet's hadith serves as a strategic solution in building a strong and harmonious spiritual character in the modern era.